Environmental and behavioural exposure pathways associated with diarrhoea and enteric pathogen detection in 5-month-old, periurban Kenyan infants: a cross-sectional study. Issue 10 (31st October 2022) - Baker, Kelly K; Mumma, Jane Awiti Odhiambo; Simiyu, Sheillah; Sewell, Daniel; Tsai, Kevin; Anderson, John David; MacDougall, Amy; Dreibelbis, Robert; Cumming, Oliver
Abstract : Objectives: The aim of this study was to test whether household environmental hygiene and behavioural conditions moderated associations between diarrhoea and enteric pathogen detection in infants 5 months of age in Kenya and pathogen sources, including latrine access, domestic animal co-habitation and public food sources. Design: Cross-sectional study utilising enrolment survey data of households participating in the Safe Start cluster-randomised controlled trial . Setting: Kisumu, Kenya. Participants: A total of 898 caregivers with 5-month (22 week ± 1 week) aged infants were enrolled in the study and completed the enrolment survey. Primary and secondary outcome measures: Outcomes were (1) caregiver-reported 7-day diarrhoea prevalence and (2) count of types of enteric viruses, bacteria and parasites in infant stool. Exposures and effect modifiers included water access and treatment, cohabitation with domestic animals, sanitation access, handwashing practices, supplemental feeding, access to refrigeration and flooring. Results: Reported handwashing after handling animals (adjusted odds ratio (aOR)=0.20; 95% CI=0.06 to 0.50) and before eating (aOR=0.44; 95% CI=0.26 to 0.73) were strongly associated with lower risk of caregiver-reported diarrhoea, while cohabitation with animals (aOR=1.54; 95% CI=1.01 to 2.34) living in a household with vinyl-covered dirt floors (aOR=0.60; 95% CI=0.45 to 0.87) were strongly associated with pathogen codetection in infants. Caregiver handwashing after child (p=0.02) or self-defecation (p=0.03) moderated the relationship between shared sanitation access and infant exposure to pathogens, specifically private latrine access was protective against pathogen exposure of infants in households, where caregivers washed hands after defecation. In the absence of handwashing, access to private sanitation posed no benefits over shared latrines for protecting infants from exposure. Conclusion: Our evidence highlights eliminating animal cohabitation and improving flooring, postdefecation and food-related handwashing, and safety and use of cow milk sources as interventions to prevent enteric pathogen exposure of young infants in Kenya. Trial registration number: NCT03468114